Aislamiento, caracterización y evaluación de Trichoderma spp. como promotor de crecimiento vegetal en pasturas de raygrass (Lolium perenne) y trébol blanco (Trifolium repens) en la hacienda La Alegría cantón Pedro Moncayo - España Imbaquingo, Cinthia Karina (2015)
Currently the fungi of the genus Trichoderma are being widely used because of the benefits that these present. They are fungi that have the ability to grow in various habitats, you can find them commonly in soil and decaying matter. These fungi have the ability to colonize the roots of plants, have also developed various mechanisms that allow them to control and parasitize other fungi. It is used in agriculture as a biological controller since it has several mechanisms of action that allow it to act as a bio-pesticide, fertilizer and biostimulant. Its role as promoter of plant growth is due to the ability to quickly colonize the roots of the plant, protecting them from attack by pathogens, resulting in an increase in growth and consistent production. The objective of this study was to isolate native strains of Trichoderma spp.. present in the soil of the hacienda "La Alegría" located in the canton Pedro Moncayo for subsequent evaluation as promoters of growth plant in raygrass and white clover pastures isolates were identified as Trichoderma harzianum and Trichoderma viride. The effect as growth promoter evaluated in previously established pasture field, made three cuts and after each cut is fertilised with Trichoderma organic matter and chemical fertilizer. The treatments that best results obtained were T1 and T6 with higher production of green and dry matter compared with the control and treatment where only used chemical fertilizer.